Literature review of image compression effects on face recognition - Padmaja, V K; Chandrasekhar, B (International Multidisciplinary Research Journal, 2012)
In this research work, a literature review is conducted to assess the progress made in the field of image compression effects on the face recognition. The DCT algorithms are considered for the review and their application is limited only to JPEG compression. In this review, progress made in the DCT algorithms of a single image, and a series images from a video, namely 2D DCT and 3D DCT respectively, along with several other algorithms in the application of face recognition are discussed in detail.